Comparisons of food intake between breast cancer patients and controls in Korean women - Kim, Eun-Young (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2007)
The purpose of this study was to compare food intakes between Korean breast cancer patients and a healthy control group. We compared the intake of nutrients of 117 food items between Korean breast cancer patients (n=97) and age matched healthy controls (n=97). Nutrient intake was estimated using a quantitative food frequency questionnaire. The mean caloric intake of breast cancer patients and healthy controls was not significantly different. Breast cancer patients consumed significantly less fat and antioxidant nutrients such as vitamin A, retinol, β-carotene, vitamin C and vitamin E when compared to the control subjects. Among the food items, the intake of eggs (p<0.01), legumes (p<0.05), vegetables (p<0.05), seasonings (p<0.001), and oils and fats (p<0.01) in breast cancer patients was significantly lower than that in the controls. These results suggest that Korean breast cancer patients consumed less amount of soy and vegetables, which are rich source of antioxidant nutrients and phytosterols. Thus, dietary guidance to increase intake of these foods may be beneficial in the prevention of breast cancer.